Pengaruh Pembelajaran Via Online Berbasis E-Learning melalui Aplikasi Zenius Terhadap Hasil Belajar Siswa SMA - Zifari, Muhammad Yogi; Sukarno, Gendut (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Nott only get a knowledge in a school environment but student also can absorb knowledge from the outside of school environment. With so many startup in education field such as Zenius, Quipper, ruangguru and etc. Course academy normally work in conventional way (face to face or via offline) which is the system kind of similar as the school system, now it can work via online (capable to access anytime and anywhere). One of the example is Zenius application which was founded in 2008 and has started for over 12 years. The research is aim to identificate how the 'e-learning' learning method influence the learning way of senior high school students. The research is about discrepancy evaluation model which is to calculate the amount of influence from online learning method. The data is collected by questionnaire and then the data is analyzed with discrepancy evaluation model. The amount of success is counted with criteria of aabsolute. Respondents of the research is senior high school students which consist of 10 grade until 12 grade students whether directly involved or not involved with zenius application. With percentage of 53,3% shows that stundent is neutral(not influence) by the influence of zenius application, as the conclusion zenius is not significantly influence the respondents learning method Keywords : influence, e-learning, study results